2013
DOI: 10.1593/tlo.12271
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress Plays a Pivotal Role in Cell Death Mediated by the Pan-Deacetylase Inhibitor Panobinostat in Human Hepatocellular Cancer Cells

Abstract: Panobinostat, a pan-deacetylase inhibitor, represents a novel therapeutic option for cancer diseases. Besides its ability to block histone deacetylases (HDACs) by promoting histone hyperacetylation, panobinostat interferes with several cell death pathways providing a potential efficacy against tumors. We have previously demonstrated that panobinostat has a potent apoptotic activity in vitro and causes a significant growth delay of hepatocellular carcinoma (HCC) tumor xenografts in nude mice models. Here, we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 59 publications
2
38
0
Order By: Relevance
“…The autophagosomes, indicated in Figure 6 by white and black arrows, are clearly visible already after 6 h and the amount increased after 48 h, especially in Hep3B cells. In addition, as previously published, the micrographs show a disorganized endoplasmic reticulum with fragmented cisternae representing a clear sign of active autophagy [ 19 ]. Based on a previously published method [ 26 , 27 ], the number of vesicles was quantified from around 100 micrographs and divided into two subgroups: early autophagosomes characterized by a double membrane and late autophagosomes as fused with endo/lysosomal vesicles including subcellular particles (Figure 5C ).…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The autophagosomes, indicated in Figure 6 by white and black arrows, are clearly visible already after 6 h and the amount increased after 48 h, especially in Hep3B cells. In addition, as previously published, the micrographs show a disorganized endoplasmic reticulum with fragmented cisternae representing a clear sign of active autophagy [ 19 ]. Based on a previously published method [ 26 , 27 ], the number of vesicles was quantified from around 100 micrographs and divided into two subgroups: early autophagosomes characterized by a double membrane and late autophagosomes as fused with endo/lysosomal vesicles including subcellular particles (Figure 5C ).…”
Section: Resultssupporting
confidence: 78%
“…Additionally, panobinostat was shown to be able to induce the activation of non-canonical apoptotic pathways; its activity could promote cell demise via endoplasmic reticulum stress [ 18 , 19 ]. Furthermore, panobinostat is responsible for the up-regulation of hsa-let-7b, a tumor suppressor miRNA, and the consequent suppression of its target HMGA2 [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study revealed that the IRE1α/XBP1 pathway may initiate downstream reactions. IRE1α activation can induce JNK phosphorylation and phosphorylated JNK can exert proapoptotic effects by activating caspase-12/4 and caspase-8 (7). Additionally, XBP1 is known to activate the transcription of CHOP (25), therefore XBP1 contributes to the induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate ER stress, dysfunction of the ER and the unfolded protein response was induced under adverse conditions, including metabolic and anaerobic stress, which disrupts the protein-folding function of the ER. Altered ER homeostasis results in an accumulation of unfolded or misfolded proteins, which ultimately leads to ER stress (6,7). The ER stress response activates cytotoxic mechanisms involving a number of regulatory cytokines associated with the onset of programmed cell death, suggesting this is a possible target in the development of chemotherapeutic agents for inducing cancer cell toxicity (8).…”
Section: Introductionmentioning
confidence: 99%